2019
DOI: 10.1001/jamainternmed.2019.0914
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Hospitals Affiliated With PPS-Exempt Cancer Centers, Other Hospitals Affiliated With NCI-Designated Cancer Centers, and Other Hospitals That Provide Cancer Care

Abstract: IMPORTANCE Congress has exempted 11 specialized cancer centers in the United States from the Prospective Payment System (PPS). These centers are also exempt from reporting many of the process-of-care and outcome measures to the Centers for Medicare & Medicaid Services that are required for hospitals in the PPS. It is not known how hospitals affiliated with PPS-exempt cancer centers differ from other hospitals affiliated with National Cancer Institute cancer centers (NCI-CCs) or other US hospitals that provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 12 publications
1
27
0
Order By: Relevance
“…And even though >80% of newly diagnosed cancer patients elect to be cared for in a community-based setting, studies from large academic medical centers have suggested that patients live longer when treated at specific academic hospital systems—a conclusion that has historically allowed such centers to avoid government-mandated payments and quality reporting processes. 1 , 2 However, a recent study has brought the rationale for this exclusionary payment benefit into question by demonstrating equivalent quality-related metrics for cancer patients treated in diverse cancer care settings. 2 Regardless, cancer-related health care expenditures have continued to rise systemically without a proportional improvement in cancer-related outcomes.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…And even though >80% of newly diagnosed cancer patients elect to be cared for in a community-based setting, studies from large academic medical centers have suggested that patients live longer when treated at specific academic hospital systems—a conclusion that has historically allowed such centers to avoid government-mandated payments and quality reporting processes. 1 , 2 However, a recent study has brought the rationale for this exclusionary payment benefit into question by demonstrating equivalent quality-related metrics for cancer patients treated in diverse cancer care settings. 2 Regardless, cancer-related health care expenditures have continued to rise systemically without a proportional improvement in cancer-related outcomes.…”
mentioning
confidence: 99%
“… 1 , 2 However, a recent study has brought the rationale for this exclusionary payment benefit into question by demonstrating equivalent quality-related metrics for cancer patients treated in diverse cancer care settings. 2 Regardless, cancer-related health care expenditures have continued to rise systemically without a proportional improvement in cancer-related outcomes. 3 In this COVID-19 era and beyond, through efforts to limit exposure risks for vulnerable cancer patients and care teams, a renewed focus on concepts of quality, value, and expertise will be necessary to allow community-based cancer programs to shoulder a greater burden for cancer care services delivered closer to home.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…35,6 Our recent study, evaluating both surgical and nonsurgical cancer care, demonstrated that few differences in hospital characteristics, patient characteristics, or outcomes exist between PCHs and National Cancer Institute (NCI)-designated Cancer Centers. 3 In this issue of Annals of Surgical Oncology, Mehta et al 7 report the results of their study evaluating outcomes of hepatic and pancreatic surgery at PCHs. They use textbook outcome (TO), a recently described composite outcome measure defined as the absence of complications, prolonged length of stay, mortality, or readmission within 90 days after discharge.…”
mentioning
confidence: 99%
“…As such, in the same way that we could never use these limited data sets to justify the continued existence of the PPS exemption for the ADCCs, we should not weaponize these data to argue that the exemption should be stripped away, as was recently done. 3 The Medicare data set is simply not the right scale for that measurement. The outcomes for a relatively small number of older cancer patients with a unique combination of stage, performance status, access, and favorable biology that afforded them the opportunity for a complex operation almost a decade ago cannot and should not be used to set (or even comment on) health policy regarding future payment models for global cancer care in the United States.…”
mentioning
confidence: 99%